Simulation of Thermal Decomposition of Calcium Oxide in Water with Different Activation Energy and the High Reynolds Number. (26th August 2022) - Memon, Abid A.; Murtaza, Saqib; Memon, M. Asif; Bhatti, Kaleemullah; Haque, Mojammel; Ali, Mohamed R.
Abstract : In this article, we are going to suggest the parameters to control the thermal decomposition in a reactor that is continuously providing a cooling environment inside the tube. For this purpose, 5 governing partial differential equations gained through mass, momentum, and energy balance laws and one ordinary differential equation are used to simulate this chemical reaction with finite element package COMSOL Multiphysics 5.6. In the simulation, the thermal decomposition of calcium oxide in the water is controlled with the use of Reynolds numbers ranging from 100 to 1000, activation energy from 75, 000 j/mol to 80, 000 j/mol, and an initial concentration of 1% to 5%. The results are presented through the graphs and tables for conversion profile, temperature distribution, enthalpy change, diffusivity, the heat source of reaction, and Sherwood and Lewis number along the axial length of the reactor. Specifically, it was found a low-speed profile at the inlet will give a 100% conversion at Re = 100 for 3% to 5% of the initial concentration. The maximum temperature and enthalpy change in the reactor are decreasing increase in the Reynolds number. Also, the decrement of the Sherwood number along the length showed that the mass diffusion is always dominant over convection-diffusion for all cases of parameters. The validation is made by comparing the numerical results with the experimental correlations.